Technological Support, Hybrid Work, and National Employment Policies: Catalysts for Worker Productivity and SDG 8 Achievement in Indonesia’s Gig Economy - Alfarizi, Muhammad; Noer, Lissa Rosdiana; Arifin Noer, Bustanul (Jurnal Ketenagakerjaan, 2025)
The rapid advancement of digital technologies has reshaped Indonesia’s labor market, with the gig economy emerging as a significant component. This study aims to analyze how technological support, hybrid work models, and national employment policies influence gig workers’ productivity and engagement, and how these factors contribute to achieving Sustainable Development Goal (SDG) 8 in Indonesia. Using a cross-sectional quantitative approach, structured questionnaires were distributed to 218 gig workers across various sectors. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to identify the strength and direction of relationships among key variables: technological support, hybrid working, national employment policy, productivity, engagement, and SDG 8 outcomes. The results show that technological support significantly improves both productivity and engagement, particularly through the availability of digital platforms and real-time work coordination tools. Hybrid work models emerged as the strongest factor influencing worker outcomes, combining flexibility with structured task management. While national employment policies had a positive impact, their effectiveness remains limited due to gaps in legal protection and social inclusion for gig workers. Importantly, the analysis reveals that engagement has a greater impact than productivity in contributing to SDG 8, emphasizing the need to foster a sense of involvement and motivation among gig workers. These findings underline the practical importance of enhancing platform responsibility, promoting digital inclusion, and redesigning employment policies to ensure fair and sustainable working conditions. This study provides actionable insights for policymakers and platform providers to better support the evolving nature of gig work in Indonesia.